2005
DOI: 10.1007/s00383-005-1466-x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent acute pancreatitis caused by malrotation of the intestine and effective treatment with laparoscopic Ladd’s procedure

Abstract: We herein report a rare case of recurrent pancreatitis caused by malrotation of the intestine. Since the age of 10 years, a female patient showed recurrent epigastralgia and was diagnosed at age 16 years as suffering from acute pancreatitis. Upper gastrointestinal series showed that the duodenal bulb was elongated and rotated caudally. Endoscopic retrograde cholangiopancreatography showed that the descending portion of the duodenum was rotated and occluded the papilla of Vater. Under laparoscopy, the duodenal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Associations with the phenomenon of a wandering liver, central nervous system abnormalities and genitourinary malformations have also been reported. Several cases of recurrent pancreatitis have also been reported in patients with malrotation [18][19][20]. In our study this was reported [18].…”
Section: Discussionsupporting
confidence: 78%
“…Associations with the phenomenon of a wandering liver, central nervous system abnormalities and genitourinary malformations have also been reported. Several cases of recurrent pancreatitis have also been reported in patients with malrotation [18][19][20]. In our study this was reported [18].…”
Section: Discussionsupporting
confidence: 78%
“…Among them are humoral proteins circulating in the plasma, endocytic receptors expressed on the cell surface and signalling receptors that can be expressed either on the cell surface or intracellularly [13]. The pro‐inflammatory cytokines such as interleukin‐1 (IL‐1), interleukin‐6 (IL‐6) or TNF‐α have been known to contribute to a variety of inflammatory condition such as ischaemic tolerance [14], rheumatoid arthritis [15], nephritis [16] and liver diseases [17]. Nitric oxide generated through inducible NO synthase (iNOS) enzymatic activity has been found to be participating in various immune and inflammatory reactions.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Another well described presentation is mal-absorption pattern associated with diarrhea, nutritional deficiencies and failure to thrive caused by bowel lymphedema resulting from lymphatic obstruction due to chronic volvulus resulting in loss of proteins from bowel lumen. 8,12,13,10 It is important to note that although many patients diagnosed as having malrotation beyond the neonatal period may be asymptomatic, they can still present with intestinal obstruction with or without strangulation at any age. 14,15 High morbidity is associated with both acute and chronic volvulus, thus surgical correction of documented malrotation is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%